NILAI PENDIDIKAN DALAM SHALAT FARDHU (Studi Tafsir Al-Misbah) - Kafrawi Kafrawi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2018)
“Shalat” means to pray or bless, while terminology, it is a typeof worship that consists of several readings and deeds, beginning with takbiratul ihram (standing) and ending with taslim (greeting). This paper discusses how the implementation of the Fardshalatto set the values of educating personalities. As a result, shalat is not only an obligation, but also expected to be able to change the values of the humans’personalitiesin their every activities or practices on this earth